Quality measurements of cuiabana-type pork sausages added with brewing by-product flours. (September 2021) - Campos, Karine Cássia Gomes de; Farias, Ananda Karla Nascimento de; Becker, Gisele; Britto, Gabriela Cristina Silva de; Soares, Willian Pinheiro; Nascimento, Edgar; Scabora, Márcia Helena; Rodrigues, Erika Cristina; Picanço, Nágela Farias Magave; Faria, Rozilaine Aparecida Pelegrine Gomes de
Abstract: The objective of this study was to evaluate the replacement of part of the pork from Cuiabana sausage by a brewery by-product on the physicochemical and microbiological properties during storage. Brewery by-product (BW) concentration influenced sausage colouration, with reduced luminosity, L*: 52.060 in the 6% (w/w) treatment compared to the 0% treatment controls (L*: 63.956). Titratable acidity showed higher (1.162 g/100 g) compared to the 0% treatment controls (1.093 g/100 g) of lactic acid. Proteins and total enzymatic fibers increased, 19.068 and 9.233 g/100 g of sample respectively. It was observed that the by-product did not interfere in the oxidation of the lipids and the best model to describe the oxidation of lipids is Van Bertalanffy model ( P < 0.05). Escherichia coli and Staphylococcus sp. levels were within the prescribed limits and Listeria monocytogenes colonies were observed. The addition of by-products had no interference on the formation of oxidation compounds in the sausage and has increased fiber content. Highlights: The brewing by-product affected the pH of sausage during storage. The instrumental texture was not altered due to addition by-product flour. The addition of brewing by-product changed the luminosity of pork sausage. There was increased ash and protein content in the sausage with 6% added flour.